1978
DOI: 10.1111/j.1365-2222.1978.tb01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity pneumonitis with antibodies to Cryptococcus neoformans

Abstract: Summary Clinical and immunological studies were made in forty‐two patients diagnosed as suffering from hypersensitivity pneumonitis at Osaka Prefectural Habikino Hospital between 1973 and 1977. All the sera from forty‐one patients tested had high litres of antibody against Cryptococcus neoformans in indirect fluorescent antibody tests, and twelve also had precipitins against Cryptococcus neoformans polysaccharide. Only about 10% of control sera from patients with otherlung diseases had low titresof antibody ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…A T. beigelii cell wall antigen produces false positive latex agglutination tests for cryptococcal antigen and cross-reacts with C. neoformans capsular polysaccharide [48,49]. Serum anti-C. neoformans antibodies have been reported in patients with hypersensitivity pneumonitis [50]. Our discovery of serum GXM in 6 5% of HIV'*' individuals in Bronx, NY, confirms a recent report of a 6% prevalence of CM in patients with AIDS in New York City [2].…”
Section: Discussionsupporting
confidence: 80%
“…A T. beigelii cell wall antigen produces false positive latex agglutination tests for cryptococcal antigen and cross-reacts with C. neoformans capsular polysaccharide [48,49]. Serum anti-C. neoformans antibodies have been reported in patients with hypersensitivity pneumonitis [50]. Our discovery of serum GXM in 6 5% of HIV'*' individuals in Bronx, NY, confirms a recent report of a 6% prevalence of CM in patients with AIDS in New York City [2].…”
Section: Discussionsupporting
confidence: 80%
“…The application of indirect immunofluorescence technique, using Cr. neoformans cells, revealed the presence of anli-Cryptoeoccus antibody in almost all sera from patients with summer-type HP (over 100 patients) and in about 65",, of sera from their family members, and contrasts with less than 10% of sera from healthy subjects and various lung diseases (Miyagawa et al, 1978). However, microbiological studies revealed no Cr.…”
Section: Discussionmentioning
confidence: 97%
“…Exposure and sensitization to such organisms might have caused the summer-type HP. AnU-Cryptococcus antibody titres changes in correlation with clinical course of summer-type HP (Miyagawa et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Nine patients with summer type HP (a unique form of HP in Ja pan) showed the following characteristics as well as the features of well-documented H P [9][10][11][12]: (1) the onset of disease in May through September (summer); (2) the recurrence of symptoms after return ing home during the hospitalization in season, and (3) anticryptococcal antibody in sera detected by an indirect immunofluorescent method.…”
Section: Subjectsmentioning
confidence: 99%